2008
DOI: 10.1016/j.juro.2008.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pelvic Floor Muscle Contraction on the Profile of Vaginal Closure Pressure in Continent and Stress Urinary Incontinent Women

Abstract: The results demonstrate that the voluntary pelvic floor muscles impose significant closure forces along the vaginal wall of continent women but not in women with stress urinary incontinence. The implication of these findings is that extrinsic urethral closure pressure is insufficiently augmented by pelvic floor muscle contraction in women with stress urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 19 publications
1
42
0
3
Order By: Relevance
“…To guarantee continence, the PFM must be able to contract strongly [9], rapidly, and reflexively [10,11]. The ability of PFM to generate rapid and strong contractions results in the generation of an adequate squeeze pressure in the proximal urethra, which maintains a pressure higher than that in the bladder, thus preventing leakage [12].…”
Section: Introductionmentioning
confidence: 99%
“…To guarantee continence, the PFM must be able to contract strongly [9], rapidly, and reflexively [10,11]. The ability of PFM to generate rapid and strong contractions results in the generation of an adequate squeeze pressure in the proximal urethra, which maintains a pressure higher than that in the bladder, thus preventing leakage [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, in a different study, Peng and colleagues did subtract the baseline pressure from their IVP measurements and in that study they found no differences in maximum IVP between women with and without SUI. 22 It appears, therefore, that the total amount of PFM force (tonic and phasic) may be more important than the increase generated with contraction efforts (phasic only), when assessing differences in PFM function between women with and without SUI. In the measurement system used in the current study, baseline pressure is influenced by individual anthropometric differences in addition to differences in the resting pressure within the vagina, and for this reason cannot be compared among the groups.…”
Section: Voluntary Pfm Contractile Strengthmentioning
confidence: 99%
“…SUI lowers the quality of life and well-being [1][2][3] of affected women and reduces their participation in sports and fitness activities [4,5]. To guarantee continence the PFM needs to contract strongly [6][7][8], rapidly and reflexively [9][10][11]. The dynamic properties of the PFM, contractility and strength, can be evaluated with various diagnostic approaches such as palpation, electromyography, dynamometry, imaging procedures [12] and thereby increase the understanding of the SUI pathomechanism.…”
Section: Introductionmentioning
confidence: 99%